2018
DOI: 10.1002/prep.201700305
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Electrically Heated Exploding Foils in Reactive Al/Ni Multilayer

Abstract: The mechanisms of metal phase transition process during electrical explosion are experimentally and theoretically investigated. Past experiments of investigation are single metal foil, such as gold, aluminum, and copper. The characteristics of aluminum‐nickel (Al/Ni) multilayer foil were investigated, which means electrical behavior and energy output. The foil was fabricated by magnetron sputtering based on ceramic substrate, and lithographically patterned into bow‐tie bridge regions. Scanning electron microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…ffi ffi ffi ffi ffi ffi at r p r expðÀ y 2 0 À z r erfc ðy 0 Þ " # ; (14) DT s ¼ T s À T 0 ¼ 2q 0 l ffi ffi ffi ffi ffi ffi at r p r : (15) Taking this solution into account, equation (12) can be rewritten in the following form…”
Section: Effect Of Decomposition Of Cuo Film On Ignition Of Organic Ementioning
confidence: 99%
See 1 more Smart Citation
“…ffi ffi ffi ffi ffi ffi at r p r expðÀ y 2 0 À z r erfc ðy 0 Þ " # ; (14) DT s ¼ T s À T 0 ¼ 2q 0 l ffi ffi ffi ffi ffi ffi at r p r : (15) Taking this solution into account, equation (12) can be rewritten in the following form…”
Section: Effect Of Decomposition Of Cuo Film On Ignition Of Organic Ementioning
confidence: 99%
“…As a result, to initiate organic EM with an open surface by a light pulse in a given spectral range, a high-power laser is needed [10]. In practice, to reduce the ignition threshold, the sample is usually covered with a transparent glass plate, and light absorbing particles ("hot spots") are introduced into the samples or laser absorbing films are applied to the EM surface [11][12][13][14][15][16][17]. Recently, works have appeared on the ignition of EM by metal particles heated to high temperatures, simulating the ignition of EM by ultrashort laser pulses, see, for example, [18].…”
Section: Introductionmentioning
confidence: 99%
“…Based on miniscule quantities of chemical reactants, NOC feature a high degree of safety [11][12][13], rapid response time, and low energy input when compared with traditional energetic materials. Of particular significance are the radical changes in performance possible through modifying the components and stoichiometries of the NOC reactants [14,15]; i. e. the key to promoting the development of NOC is to select suitable energetic materials. Thermites, a subset of metastable intermolecular composites (MIC) composed of Al and metal oxides (e. g., CuO [16], Fe 2 O 3 [17], and MoO 3 [18]), have been widely utilized in the fabrication of thermal NOC.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of the premixed layer have a profound impact on the energy storage and release of the bridge foil. Wang [31] et al carried out experimental research on the electric explosion performance and flyer driving performance of Al/Ni multilayer foil and analyzed the internal mechanism of the performance of Al/Ni multilayer foil, which was superior to that of a traditional Cu film exploding foil because of the crystallization reaction of Al and Ni. Their results also showed that the higher the premixed layer ratio was, the more energy was released from the Al/Ni alloy, and the faster the plasma flame advance.…”
Section: Introductionmentioning
confidence: 99%